2015
DOI: 10.1308/rcsann.2015.0012
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between body temperature and serum lactate levels in hip fracture patients?

Abstract: INTRODUCTION Hyperlactataemia is associated with adverse outcomes in trauma cases. It is thought to be the result of anaerobic respiration during hypoperfusion. This produces much less energy than complete aerobic glycolysis. Low body temperature in the injured patient carries an equally poor prognosis. Significant amounts of energy are expended in maintaining euthermia. Consequently, there may be a link between lactate levels and dysthermia. Hyperlactataemia may be indicative of inefficient energy production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Glycolysis is a widespread phenomenon and is the basis of diverse brain activities. It is reported that more energy is required to maintain pyrexia [27], which has been proved by this experiment. From Figure 4 and Figure 5, we can easily find an increase in glycolysis in yeast-induced pyretic rat, which causes a reduced content in metabolites.…”
Section: Discussionsupporting
confidence: 71%
“…Glycolysis is a widespread phenomenon and is the basis of diverse brain activities. It is reported that more energy is required to maintain pyrexia [27], which has been proved by this experiment. From Figure 4 and Figure 5, we can easily find an increase in glycolysis in yeast-induced pyretic rat, which causes a reduced content in metabolites.…”
Section: Discussionsupporting
confidence: 71%
“…A large-scale multi-center retrospective cohort study by Faizi et al 13 stratified 1162 patients into groups based on body temperature (>37.5°C pyrexial, 36.5-37.5°C euthermic, <36.5°C low body temperature). Temperature data was taken via tympanic thermometers which were regularly calibrated by the units’ medical physics department.…”
Section: Resultsmentioning
confidence: 99%
“…There is a link between hypothermia and poor outcome—whist the studies reviewed are often contradictory of which outcome measure is most affected, they all demonstrate a negative association with periods of lower temperatures in the hip fracture population. Increasing serum lactate and its link to poor outcome, 13 unplanned admission and mortality are all demonstrated to be impacted by lower body temperatures. Interestingly, the literature supports a view that there is more than one opportunity for cooling to be reversed and opportunities to correct temperature control exist at all parts of the patient episode.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] A reduction in core body temperature increases oxygen consumption and increases stress on cellular processes, resulting in high mortality. [ 9 ] Therefore, blood loss, peripheral vasoconstriction and decreased cardiac output, cause imbalance between the demand and supply of oxygen, especially in vital organs; and in the elderly with cardiovascular disease, heart failure and acute myocardial infarction may occur during postoperative hypothermia. [ 10 , 11 ] Despite heating protocols during the perioperative phases, there are several factors that cause hypothermia; such as, general anesthesia that inhibits the reflections of thermoregulation, the administration of intravenous fluids used to irrigate the wound, the temperature in the operating room; the nature, extent and duration of the surgical procedure, age over 60, low body weight, and American Society of Anesthesiologists (ASA) Classification.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperative hypothermia may decrease wound healing, increase the risk of surgical site infections (SSI) and increase intraoperative bleeding and cardiovascular morbidity [8] . A reduction in core body temperature increases oxygen consumption and increases stress on cellular processes, resulting in high mortality [9] . Therefore, blood loss, peripheral vasoconstriction and decreased cardiac output, cause imbalance between the demand and supply of oxygen, especially in vital organs; and in the elderly with cardiovascular disease, heart failure and acute myocardial infarction may occur during postoperative hypothermia [10,11] .…”
Section: Introductionmentioning
confidence: 99%